2019
DOI: 10.1109/access.2019.2919534
|View full text |Cite
|
Sign up to set email alerts
|

Survey on the Incorporation of NDN/CCN in IoT

Abstract: Named data networking (NDN) has emerged as a component of the Future Internet architecture to support scalable content distribution, mobility, security, and trust; as well as to provide access to information irrespective of its physical location. The NDN, and previously content-centric networking (CCN), has been considered as the enabler to address various Internet of Things (IoT) challenges, with the potential to outperform the current IP paradigm in many dimensions. The requirements and challenges of the IoT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(32 citation statements)
references
References 93 publications
0
30
0
2
Order By: Relevance
“…Information-centric networking (ICN) [22][23][24][25] is considered a promising approach for Internet of Things [26][27][28]. Recently, a number of works have been investigated to explore the benefits of ICN for IoT [10,11,[29][30][31][32].…”
Section: Related Workmentioning
confidence: 99%
“…Information-centric networking (ICN) [22][23][24][25] is considered a promising approach for Internet of Things [26][27][28]. Recently, a number of works have been investigated to explore the benefits of ICN for IoT [10,11,[29][30][31][32].…”
Section: Related Workmentioning
confidence: 99%
“…According to previous studies, the edge architecture is an appropriate one for IoT where the edge node is deployed to serve as a middleware connecting applications with one or several WSNs. State-of-the-art studies [3,4] suggested that the edge node is one of the best options to serve as a caching node for IoT data.…”
Section: Application Modelmentioning
confidence: 99%
“…We implement a prototype of CCR in Contiki CCN [35] on the top of ProbCache with LRU (Least-Recently-Used) [3,18] and LCD (Leave Copy Down) [4] with LRU. We then perform simulations using COOJA simulator [35] with an edge node and 1500 sensors of temperature, humidity, and accelerometer types.…”
Section: Performance Evaluationmentioning
confidence: 99%
See 2 more Smart Citations